Sacred Habitat: Nature and Catholicism in the Early Modern Spanish Atlantic by Ran Segev. University Park: The Pennsylvania State University Press, 2023. xvi + 213 pp. $ 129.95 hardcover - Marroquín Arredondo, Jaime (Church history, 2024)
Sacred Habitat: Nature and Catholicism in the Early Modern Spanish Atlantic by Ran Segev. University Park: The Pennsylvania State University Press, 2023. xvi + 213 pp. $ 129.95 hardcover. - Volume 93 Issue 3.